National TB Elimination Program (NTEP): at a glance - Susmita Kundu; Rahul Ghosh (The Journal of Association of Chest Physicians, 2022)
Abstract India has the highest burden of tuberculosis worldwide. Over the last six decades there was evolution of national programs on tuberculosis. The present national program on tuberculosis emphasized on elimination and prevention of tuberculosis.